High-Definition X-Ray Fluorescence: Applications. (7th August 2008) - Gibson, Walter M.; Chen, Z. W.; Li, Danhong
Abstract : Energy dispersive X-ray fluorescence (EDXRF) is a well-established and powerful tool for nondestructive elemental analysis of virtually any material. It is widely used for environmental, industrial, pharmaceutical, forensic, and scientific research applications to measure the concentration of elemental constituents or contaminants. The fluorescing atoms can be excited by energetic electrons, ions, or photons. A particular EDXRF method, monochromatic microbeam X-ray fluorescence (Mμ EDXRF), has proven to be remarkably powerful in measurement of trace element concentrations and distributions in a large variety of important medical, environmental, and industrial applications. When used with state-of-the-art doubly curved crystal (DCC) X-ray optics, this technique enables high-sensitivity, compact, low-power, safe, reliable, and rugged analyzers for insitu, online measurements in industrial process, clinical, and field settings. This new optic-enabled Mμ EDXRF technique is known as high-definition X-Ray fluorescence (HD XRF). Selected applications of HD XRF are described in this paper including air particulate analysis, analysis of body fluid contamination at ppb levels, elemental mapping of brain tissue and bone samples, as well as analysis of toxins in toys and other consumer products.